If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+2-1=(2x+5)/3
We move all terms to the left:
x+2-1-((2x+5)/3)=0
We add all the numbers together, and all the variables
x-((2x+5)/3)+1=0
We multiply all the terms by the denominator
x*3)-((2x+5)+1*3)=0
We add all the numbers together, and all the variables
x*3)-((2x+5)=0
Wy multiply elements
3x^2=0
a = 3; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·3·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:$x=\frac{-b}{2a}=\frac{0}{6}=0$
| x/x+1+x/x-2=1 | | 5x+6x-2=128 | | s=(25-2)180 | | b/4+-10=-6 | | 6s-41=73 | | -12(y+1)+6(3y-3)=5(y-6)+10 | | (x=3)÷2=5 | | 5(5-6x)=-245 | | 3/2x=-14 | | 7(5x+2)=3x+14 | | 4.1+b=12.8 | | -(x+2)=5x+3x=11 | | 12+10x-12-6x+6=12+(10x-12)-6x+6 | | 17n-4-11n=18n-7n+8 | | 24=3x2 | | 22(x-4)=-3x | | –2x–1=9 | | 7z+4=8 | | 5+2x=2x+ | | 3x−1=38 | | 25+3(x+4)=4x+122 | | 5s-46=59 | | 7x-(-10)=10 | | 2x–2=–6 | | (4.129+x)/2=4.086 | | 100−2x=84 | | 5x+2.5=-7.5 | | 3x-7=60-x | | -122y=244 | | 12=(1/2)(4x+16) | | x–3=–4. | | 7/3x+1/3x=3x+9/3+8/3x |